Surveillance of Aedes Mosquitoes in a University Campus in Kuala Lumpur, Malaysia - Wan-Norafikah, O.; Chen, C.D.; Soh, H.N.; Lee, H.L.; Nazni, W.A.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2009)
Ovitrap surveillance was initiated for eight continuous weeks to determine the distribution and abundance of Aedes sp. mosquitoes in the University of Malaya campus, Kuala Lumpur, and the impact of meteorological conditions on the Aedes populations. Two study areas within the campus were selected: Varsity Lake and Seventh Residential College. The abundance of Aedes populations in Varsity Lake was indicated by ovitrap index (OI) which ranged from 60.00 - 90.00. The mean number of larvae per ovitrap of Aedes albopictus in Varsity Lake ranged from 11.23 ± 2.42 - 43.80 ± 6.22. On the other hand, the outdoor OI for Seventh Residential College ranged from 73.33 - 93.33, respectively, while the mean number larvae per ovitrap for this area ranged from 19.33 ± 4.55 - 35.27 ± 5.46, respectively. In addition, the indoor OI of Seventh Residential College ranged from 0.00 - 30.00, while the mean number of larvae per ovitrap for Ae. albopictus ranged from 0 - 5.90 ± 3.55. There was no significant difference (p > 0.05) of Ae. albopictus population between Varsity Lake and Seventh Residential College. The studies showed a correlation between OI and mean number of larvae per ovitrap for outdoor Ae. albopictus populations in Varsity Lake and Seventh Residential College (r = 0.794). There was also a correlation between the mean larvae number per ovitrap of Ae. albopictus obtained from eight weeks indoor ovitrap surveillance in Seventh Residential College with rainfall (r = 0.584). However, there was no correlation between the mean larvae number per ovitrap of Ae. albopictus in both study areas with temperature and relative humidity. Aedes aegypti mosquitoes were found neither indoor nor outdoor in both study areas. This study indicated that the principal dengue vector in the university campus was most likely Ae. albopictus.